Energy and exergy analysis of the PVT system: Effect of nanofluid flow rate. (15th July 2018) - Fayaz, H.; Nasrin, R.; Rahim, N.A.; Hasanuzzaman, M.
Highlights: Investigation of PVT system with 3D numerical modeling is done. Novel design of thermal collector is introduced with MWCNT nanofluid. Using flow, electrical efficiency improvement is 10.72% experimentally and 12.25% numerically. Thermal efficiency obtained is 81.24 and 79.1% numerically and experimentally. Using nanofluid, overall efficiency enhancement is 6.26% numerically and 5.73% experimentally. Abstract: Solar energy is one of the promising resources to fulfil the energy demands to some level in place of fossil fuels to avoid environmental pollution. The efficiency of solar technology, e.g. photovoltaic panels, thermal systems or a combination of both technologies as photovoltaic thermal is a concern to increase at an optimum level. A three-dimensional numerical analysis of PVT systems using water and MWCNT-water nanofluid has been completed with FEM based software COMSOL Multiphysics®. A numerical investigation has been validated by the indoor experimental research at different mass flow rates of 30 to 120 L/h while keeping solar irradiation fixed at 1000 W/m 2, inlet fluid and ambient temperature at 32 and 25 °C, respectively. Percent improvement of electrical efficiency of PV with nanofluid cooling at flow rate 120 L/h is obtained about 10.72 and 12.25% of numerical and experimental cases respectively. Optimization of the nanofluid for weight concentration is achieved at 0.75% MWCNT-water. Solar cell temperature reduces about 0.72 °C experimentally and 0.77 °C numerically per 10 L/h flow rate increment. Approximately 7.74 and 6.89 W thermal energy is enhanced per 10 L/h flow rate increment in numerical and experimental studies respectively. Percentage increment of thermal efficiency is found as 5.62% numerically and 5.13% experimentally for PVT system operated by water/MWCNT nanofluid with compared to water.